CODE SWITCHING ANALYSIS IN SADENA DAN SANDRA NOVEL - Maria Yasinta Juita; Komang Dian Puspita Candra; Ida Bagus Gede Nova Winarta (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2022)
Abstract—This study aims to determine the types of code switching occurred in Sadena dan Sandra Novel. The data source of this study was taken from Sadena dan Sandra Novel by Wulanfadi. In collecting the data, the researcher was used observation research method. This study were analyzed qualitatively by using theory from Hamers and Blanc (2000) which mention three types of code switching, they are inter-sentential switching, intra-sentential switching and extra sentential code switching or tag switching. The result of this study showed that all types of code switching occurred in this novel, they are; inter-sentential switching, intra-sentential switching, extra sentential switching or tag switching, and the most dominant type is intra-sentential switching.